2019
DOI: 10.33423/jop.v19i5.2511
|View full text |Cite
|
Sign up to set email alerts
|

Stressed-out, Self-isolated, and Hyper-connected: Teaching Today’s Learners

Abstract: Today's learners bear a stress load of which their predecessors may never have dreamed. College students in the United States have financial and economic pressure. They have the perception that academic success is the only path to career success. Additionally, today's college students have become adults in an age where electronic connection is expected. An initial study found that college students reported academics as a significant pressure and that connecting face-to-face with and belonging to a group of pee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Education theory supports the importance of service-learning, especially in today's educational context. Scholars suggest that today's college students (16-24 years old) learn differently than college students of previous generations did (Brown, 2018;Coomes & DeBard, 2004;Howe & Strauss, 2007;Landin, 2019;Nicholas, 2019;Taylor, 2010). For example, many students adopt a consumer and outcome orientation toward college and are intellectually disengaged from traditional lecture-based courses.…”
Section: Service-learning Theorymentioning
confidence: 99%
“…Education theory supports the importance of service-learning, especially in today's educational context. Scholars suggest that today's college students (16-24 years old) learn differently than college students of previous generations did (Brown, 2018;Coomes & DeBard, 2004;Howe & Strauss, 2007;Landin, 2019;Nicholas, 2019;Taylor, 2010). For example, many students adopt a consumer and outcome orientation toward college and are intellectually disengaged from traditional lecture-based courses.…”
Section: Service-learning Theorymentioning
confidence: 99%
“…Unlike the other attributes that can be viewed as positively affecting grades, unrestrained achievement will likely have a negative impact on grades. This is because the high levels of unrestrained achievement that are typically found in the current population in higher education (Landin, 2019; Pisarik et al, 2017) could lead to their attempt to essentially “game” the course through the use of shortcuts in order to succeed at any cost (Hamlen, 2012). When students make use of shortcuts, they may not acquire a thorough understanding of foundational concepts that could lead to lack of comprehension of subsequent topics.…”
Section: Attribute Differences Between High- and Low-grade Performersmentioning
confidence: 99%
“…MAB that are common in the current higher education population that are found to affect academic grade performance include self-efficacy (Becker and Gable, 2009), neutralizing attitudes (Seemiller and Grace, 2016), fear of failure (Haider et al, 2015;Pitt et al, 2018), moral inhibition (Williams, 2015), unrestrained achievement (Landin, 2019), peer pressure (Toothaker and Taliaferro, 2017), and distributive justice (Kovacevic et al, 2013). Prior literature alludes to how each of the MAB listed above can differ between high and low academic grade performers.…”
Section: Attribute Differences Between High-and Low-grade Performersmentioning
confidence: 99%
“…Pre-pandemic college students of the late 2010's experienced greater levels of stress than college students from 20 years ago (Landin, 2019). A study of mental health illnesses among college students showed that the number of mental health reports were significantly greater in 2019 when compared to the number of reports that occurred just four years prior in 2015 (Oswalt et al 2020).…”
mentioning
confidence: 99%